Javan Primates’ Abundance and Distribution In The Mekarbuana and Sukasari, Mount Sanggabuana, West Java - Rifda Humayra; Sinta Sri Delvi; Muhammad Farhan; Zahra Davina Salsabilla; Nadzifa Febi Azzura; Syifa Putri Azzahra; Meina Merintan; Nadia Fitriani; Sri Suci Utami Atmoko (Universitas Nasional Jakarta, 2026)
Mount Sanggabuana is a limited production forest area with potential primate diversity in West Java. This study aims to determine the distribution and abundance of primates in the Mekarbuana area, Karawang, and Sukasari area, Purwakarta. The study was conducted in October-November 2024 in Mekarbuana and September 2025 in Sukasari using the Recce method, with a total of eight observation routes. Data collected included the number of individuals, groups, coordinate positions, and primate activity. The encounter rate was calculated as the number of individuals or groups per kilometer of route. The results showed that in Mekarbuana, 4 primate species were recorded, namely Trachypithecus mauritius with an abundance of 7.47 ind/km and a relative abundance of 67%, Presbytis comata with an abundance of 2.36 ind/km and a relative abundance of 21%, Hylobates moloch with an abundance of 0.98 ind/km and a relative abundance of 9%, and nocturnal primate Nycticebus javanicus with an abundance of 0.39 ind/km and a relative abundance of 4%. In Sukasari area, 3 species were recorded, namely Trachypithecus mauritius with an abundance of 2.75 ind/km and a relative abundance of 89%, Hylobates moloch with an abundance of 0.23 ind/km and a relative abundance of 5%, and Nycticebus javanicus with an abundance of 0.23 ind/km and a relative abundance of 6%. Trachypithecus mauritius was the dominant species in both locations. Differences in primate abundance in both locations were influenced by food availability, vegetation structure, and the level of habitat disturbance. This research provides baseline data for primate conservation management on Mount Sanggabuana.